Individual Values and SME Environmental Engagement. Issue 4 (April 2020) - Schaefer, Anja; Williams, Sarah; Blundel, Richard
We study the values on which managers of small and medium-sized enterprises (SMEs) draw when constructing their personal and organizational-level engagement with environmental issues, particularly climate change. Values play an important mediating role in business environmental engagement, but relatively little research has been conducted on individual values in smaller organizations. Using the Schwartz Value System (SVS) as a framework for a qualitative analysis, we identify four "ideal-types" of SME managers and provide rich descriptions of the ways in which values shape their constructions of environmental engagement. In contrast to previous research, which is framed around a binary divide between self-enhancing and self-transcending values, our typology distinguishes between individuals drawing primarily on Power or on Achievement values and indicates how a combination of Achievement and Benevolence values is particularly significant in shaping environmental engagement. This demonstrates the theoretical usefulness of focusing on a complete range of values. Implications for policy and practice are discussed.